Investigating the Effectiveness of Technology-Enhanced Language Learning Tools in Supporting Second Language Acquisition - Christiana Darkoah; Levina Nyameye Abunya; Edward Owusu; Victoria Ogunnike Faleke (Journal of Education and Learning Technology)
The level of attainment of second language (L2) proficiency in children differs. While some attain it early, others face several challenges in achieving success in language proficiency. The variance raises inquiries into the factors influencing language learning outcomes among young learners. Consequently, this paper delved into the correlation between young learner’s access to technological tools and devices at home and their proficiency levels in their second language. Twenty-five participants were randomly selected from KNUST Primary School in Kumasi, Ghana. Employing a qualitative research approach with a corresponding phenomenological research design, the study conducted semi-structured interviews with twenty-five out of forty-three learners in a basic three class. Through thematic data analysis, the study revealed a rising trend of learners utilizing technology-enhanced language learning tools beyond conventional classrooms, indicating a shift towards integrated and personalized language learning. Furthermore, the study discovered that effective utilization of technology can strengthen vocabulary and communication skills, with various tools like language apps, television channels, smartphones, and computers playing roles in facilitating Second Language Acquisition (SLA). The study recommended ensuring equitable access to technology is essential, necessitating investments in infrastructure and resources. Educators should undergo professional development to integrate technology-enhanced language learning tools effectively. Collaboration among researchers, educators, and developers is pivotal for creating high-quality tools that cater to diverse learner needs. The paper highlights the critical role of technological tools in SLA among young learners, shedding light on how access to and effective use of technology can improve vocabulary and communication skills.